HDFS with cache system – a paradigm for performance improvement - Dr. Suhas Raut, Ms. Archana Kakade (International Journal of Scientific Research and Management (IJSRM), 2014)
Due to online activities and use of resources related to computing, data is being generated at an enormous rate. To access andhandle such huge amount of data spread, distributed systems is an efficient mechanism. One such mechanism is a Hadoop distributed filesystem (HDFS). However HDFS faces performance drawback. Hence need is felt improve upon the performance. In this paper we arepresenting a new paradigm for improving small file processing in HDFS. The paradigm shift is to use cache information. It is known thataccessing data from cache is much faster as compared to disk access. The cache memory is used to store frequently accessed data & henceprocess it much more quickly. This paper describes the system architecture that aims to provide a cache system to HDFS, we can avoidunnecessary trips HDD to fetch data and thus avoid delay